PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN INOVASI KEWIRAUSAHAAN OLAHAN SINGKONG DI KAMPUNG YOMAIMA DISTRIK NAPUA JAYAWIJAYA, PAPUA - Wulandari, Siti Latifa; Takdir, Nuraisyah; Soni, Aprianto; Sabriani, Sabriani (Universitas Padjadjaran, 2024)
There are strategies to improve the quality of human resources, one of which is by improving entrepreneurship training programs. The potential of community agricultural products can be processed into products that are marketable and become entrepreneurial innovations. The development of increasingly sophisticated technology and information is currently not well understood by the general public, especially rural communities. This entrepreneurship development activity was carried out in Yomaima Village, Napua District. This village is located in Jayawijaya Regency, Papua Mountain Province. This activity was attended by 25 Yomaima village residents, 3 facilitators, and 16 KKN students. The implementation method will empower local communities with innovative activities in processing cassava, providing education on processing cassava into croquettes with various flavors, as well as providing quality products and training on cassava croquette production. The results of this activity show that public knowledge has increased. The community's interest in learning is to change the wealth of cassava raw materials in the village into processed products that have high economic value and can ultimately help the economy and improve the quality of life of Yomaima village residents. The results of these activities must be continued in further stages of collaboration with Yomaima Village as the fostered village, so that this activity is sustainable and routinely carried out. Therefore, we need to form a group of SMEs that focus on improving community entrepreneurship. This concerns the development of innovative technological products from cassava raw materials such as cassava croquettes which can increase income in the future.Banyak cara yang bisa dilakukan untuk meningkatkan kualitas sumber daya manusia, salah satunya dengan meningkatkan program pelatihan kewirausahaan. Potensi hasil pertanian masyarakat dapat diolah menjadi produk yang layak dipasarkan dan menjadi inovasi wirausaha. Perkembangan teknologi dan informasi yang semakin canggih saat ini kurang dipahami dengan baik oleh masyarakat umum, khususnya masyarakat pedesaan. Kegiatan pengembangan kewirausahaan ini dilaksanakan di Kampung Yomaima, Distrik Napua. Kampung ini terletak di Kabupaten Jayawijaya, Provinsi Pegunungan Papua. Kegiatan ini diikuti oleh 25 orang warga Kampung Yomaima, 3 orang fasilitator, dan 16 orang mahasiswa KKN. Metode pelaksanaannya yaitu dengan memberdayakan masyarakat lokal dengan kegiatan inovasi pengolahan bahan baku singkong, memberikan penyuluhan pengolahan singkong menjadi kroket dengan berbagai rasa, serta memberikan produk berkualitas dan pelatihan produksi kroket singkong. Hasil dari kegiatan ini menunjukkan bahwa pengetahuan masyarakat mengalami peningkatan. Minat belajar masyarakat adalah mengubah kekayaan bahan baku singkong yang ada di desa menjadi produk olahan yang mempunyai nilai ekonomi tinggi dan pada akhirnya dapat membantu perekonomian serta meningkatkan kualitas hidup warga Kampung Yomaima. Hasil dari kegiatan ini harus dilanjutkan pada kerjasama tahap pertama dengan Desa Yomaima sebagai desa binaan, agar kegiatan ini berkelanjutan dan rutin dilaksanakan. Setelah itu, kita perlu membentuk kelompok UKM yang berfokus pada peningkatan kewirausahaan masyarakat. Hal tersebut menyangkut pengembangan produk teknologi inovatif dari bahan baku singkong seperti kroket singkong yang dapat meningkatkan pendapatan publik di masa depan.